Exploring Geographical Indication Protection Arrangements: Socialization for the PKK Team in Tanggamus Regency - Ria Wierma Putri; Yunita Maya Putri; Tristiyanto Tristiyanto; Dorothy Rouli Pandjaitan (Probono and Community Service Journal, 2023)
Geographical Indications (GIs) are collective intellectual property rights that protect place names or designations used to identify goods with unique qualities, properties, or reputations from specific geographic areas. GIs were adapted from the provisions of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement, which provides national and international legal protection to registered GI products. GIs are particularly important for developing countries like Indonesia, as they help maintain the authenticity of local products, often known by other regions, especially agricultural products. However, conflicts between trademark regulations and GIs have hindered the growth of GIs in Indonesia. In response to this issue, the Indonesian government enacted Law No. 20 of 2016 on Trademark and Geographical Indications, granting GIs equal status to trademarks. Despite this, it has become evident through discussions with relevant agencies that the Trademark Law and GIs are not widely known by the community, including the Family Welfare Movement Organization (PKK) in Tanggamus Regency. Ironically, Tanggamus, one of the regencies in Lampung Province, holds GI certification for its Robusta coffee. The PKK, with its strategic role, can play a vital part in disseminating information about GIs to the community, including remote villages where coffee farmers reside. Therefore, this community service program aims to provide information about GI regulations to PKK members, hoping that they will help reach a wider audience in Tanggamus Regency.